PENGARUH LIKUIDITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN PENGHARGAAN ANNUAL REPORT AWARD 2019 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015 – 2019 - Deasy Femayona Devi; Siti Mardianty (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to examine and analyze the effect of liquidity on corporate social responsibility. The independent variable is liquidity by measuring the current ratio and liquidity by measuring the cash ratio while the dependent variable is corporate social responsibility. The object of research in this study is the 2019 Annual Report Award winning companies listed on the Indonesia Stock Exchange in 2015 - 2019. The population of this study were 32 companies that won the 2019 Annual Report Award listed on the Indonesia Stock Exchange in 2015 - 2019. The research sample was selected using the method purposive sampling with certain criteria and obtained as many as 14 companies that meet the criteria. The analytical method used is multiple regression analysis. The results of the analysis show that the liquidity variable using the current ratio measurement has a significant negative effect on corporate social responsibility, the liquidity variable using the cash ratio measurement has a significant negative effect on corporate social responsibility, this shows that the smaller the liquidity of a company, the disclosure of corporate social responsibility information will be more low. Meanwhile, simultaneously, the liquidity variable using the current ratio and cash ratio measurements has a significant negative effect on corporate social responsibility, meaning that the higher the company's liquidity, the higher the disclosure of corporate social responsibility information will be.